PENGARUH THIN CAPITALIZATION DAN FAKTOR LAINNYA TERHADAP PENGHINDARAN PAJAK - Gouwvara, Nathasya; Susanty, Meinie (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2023)
The purpose of this research is to determine the affect of thin capitalization, profitability, capital intensity, advertising expense, firm size, firm age, sales growth, and foreign ownership on tax avoidance.The data used in this research were from the financial statement of the manufacturing companies that were listed consistently on the Indonesia Stock Exchange (IDX) from 2019 until 2021. The sampel of this research are 132 years of data from 44 samples manufacturing companies that selected by using purposive sampling method. This research used multiple linear regression models to analyze data. This research results had proven that the thin capitalization and profitability have an influence on tax avoidance. While the capital intensity, advertising expense, firm size, firm age, sales growth, and foreign ownership do not have a influence on tax avoidance.